Rapidly expanding saphenous vein graft myoctic aneurysm causing ST-elevation myocardial infarction: a case report. Issue 2 (20th February 2020) - Ray, Max; McGee, Michael; Collins, Nicholas; Cooke, Heather
Abstract: Background : Mycotic aneurysms of coronary vein grafts are rare and associated with high mortality. They are most commonly a result of surgical or percutaneous intervention, and present with complications including myocardial infarction (MI), infective endocarditis. A recent literature review identified 97 cases of mycotic coronary aneurysms in total. Case summary: A 49-year-old man with a history of coronary artery bypass grafting and septic arthrithis presented with chest pain and fevers and ST elevation on electrocardiogram. Urgent angiogram showed an aneurysmal saphenous vein graft from the PL branch to PDA—no acute intervention was performed due to concern about bacteraemia. Methicillin-sensitive Staphylococcus aureus was grown in urine and blood but no focus of infection was identified. Despite treatment with antibiotics and antiplatelets, the patient returned with evidence of expansion of the SVG aneurysm requiring surgical resection. Discussion : This case highlights the difficulty in treating acute coronary syndromes involving mycotic aneurysms. Multimodal imaging approaches are useful to identify suspected infection, but false negatives occur. Due to high risk of rupture or haemorrhage, there are limited options for urgent reperfusion in cases of MI with mycotic aneurysm, demonstrating the need for an individualized approach and close follow-up.